Shifting Muslim Gorontalo Family Commitments in the Era of Social Media: A Socio-Legal Approach - Yasin, Dikson T.; Ghofur, Abdul; Fanani, Muhyar; Nurhadi, Agus (Ushuluddin, Adab, and Dakwah Faculty of State Islamic University Ponorogo, 2023)
In the era of social media, the current reality has led to a deviation in individual behavior within families. Family systems relying heavily on technology have shifted from traditional to modern. The research aims to explain why social media can lead to divorce in Gorontalo Religious Court. This study constitutes empirical research (field research). The research was meticulously conducted through direct fieldwork. The approach employed in this study is a social approach. The researcher directly investigates and deeply describes the commitment of married couples in household life and the influence of social media. To obtain valid data, the researcher used observation techniques for data collection. The researcher observed within the scope of scientific activities during the observation activities. In this case, the researcher observed 10 pairs of Muslim families in the city of Gorontalo, focusing on how the commitment of Gorontalo Muslim families has shifted. The number of respondents interviewed by the researcher was approximately 10 Muslim families, consisting of 5 husbands and 5 wives each. Finally, Documentation collected data from Gorontalo Religious Court judgments on divorces during 2021. Results of the research found that social media has an impact on two things, namely: 1) the fragility of Gorontalo Muslim family commitments due to tolerance of extramarital behavior in Gorontalo Muslim families, and 2) a shift in divorce orientation among Gorontalo Muslim families, where about 13.8% of divorce cases are caused by infidelity through social media.